Polarization surpassed: Perspectives of Portuguese gatekeepers on immigration and cultural relativism across the political spectrum - Dias, J. F. (Journal for Deradicalization, 2024)
This qualitative study investigates how Portuguese societal gatekeepers from across the political spectrum address and mitigate polarization surrounding immigration and cultural relativism. Drawing on in-depth interviews with 20 influential figures in politics, media, and civil society, the research uncovers how these gatekeepers foster inclusive narratives that emphasize human rights and social cohesion, distinguishing Portugal from other European contexts marked by highly polarized immigration debates. Despite diverse ideological positions, the findings reveal a shared commitment to tempering extreme views through dialogue, mutual understanding, and strategic framing of immigration as an opportunity for cultural enrichment rather than a societal threat. The study demonstrates how this consensus-driven approach counteracts divisive rhetoric and populist exploitation of immigration issues, enabling Portugal to maintain societal cohesion in the face of growing multiculturalism. Unlike many European countries where populist movements fuel polarization, Portuguese gatekeepers strategically leverage integration policies to reinforce belonging and universal human rights. This model not only reduces alienation but also minimizes the risk of radicalization, emphasizing the importance of balancing cultural diversity with adherence to shared democratic values. The findings underscore the critical role of local actors in counter-radicalization (P/CVE) efforts by promoting inclusive, human-rights-centered approaches that safeguard vulnerable groups while fostering resilience against extremism. By offering actionable insights for policymakers and practitioners, this research provides a framework for other nations grappling with similar challenges. The Portuguese experience illustrates how context-sensitive strategies rooted in inclusivity and dialogue can build cohesive, multicultural societies that uphold universal freedoms while celebrating diversity.